Pollutant emissions of diesel engines powered by diesel fuel mixed with ethanol - Matuszewska, Anna; Odziemkowska, Małgorzata; Czarnocka, Joanna (Studia Ecologiae et Bioethicae, 2013)
Bioethanol is an oxygen compound added to gasoline. Research into the possibility of applying it to diesel oil is conducted. It is assumed that such fuel could help reduce the emission of gaseous and particulate matter in comparison with conventional fuels. This paper presents the results of the authors’ chassis dynamometer test for biofuel containing 15% bioethanol. Emissions of carbon monoxide (CO), nitrogen oxides (NOx), hydrocarbons (THC), and particulate matters (PM) were related to diesel oil emissions.